Pemanfaatan Website Sebagai Media Promosi Dalam Pengembangan UMKM Rumah Jahit Novi&Co.id - Novi Kristina Zalukhu; Olifia Syafriani; Suci Aprima Dani; Zulfitri Yani; Sularno Sularno (CV. ITTC INDONESIA, 2026)
The development of information technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to utilize digital media to support business activities. However, many MSMEs have not yet optimally utilized digital technology, particularly in promotion and information dissemination. One of the digital media that can be used is a website, which provides broad and easy access to information for the public. Rumah Jahit Novi&Co.id is a tailoring service MSME that has utilized a website as a promotional medium. This study aims to analyze the utilization of websites as a promotional tool in supporting the development of Rumah Jahit Novi&Co.id. The research employed a descriptive qualitative method with data collected through observation, interviews, and documentation. The results indicate that website utilization helps introduce available services, display tailoring portfolios, improve business credibility, and expand promotional reach to potential customers. In addition, the website facilitates customers in obtaining information regarding the services offered. Therefore, website utilization can be an effective strategy in supporting MSME development and enhancing the competitiveness of tailoring service businesses in the digital era.